Biomechanical analysis of a rhythmic gymnastics jump performed using two run-up techniques - Coppola, S.; Albano,. D.; Sivoccia, I.; Vastola, R. (Journal of Physical Education and Sport, 2020)
The aim of this study is to describe the split leap performed using two types of run-ups. The first technique is a simple run (RT), and the second technique is the chassè (CT). The research was carried out through thekinematic analysis of the jump. The sample consisted ofa one 12-year-old gymnast (category A4) practicing rhythmic gymnastics at a competitive level for 4 years. A passive marker optoelectronic system, consisting of six BTS Smart-D cameras, was used for the kinematic analysis. In addition, two BTS Vixta cameras were used for the video support. Moreover, two force platforms were used to detect the contact and take-off.The CASTprotocol was used for the acquisition and evaluation of the data. For each technique, the gymnast performed six trials. Data processing was performed by the Smart Analyzer software. The motor task was divided into three phases: run-up, take-off, and flight phases.Forthe three phases, the position, speed, and linear acceleration of the sacrum were examined.During the take-off and flight phases, speed and angular acceleration of the thigh segmentwere analyzed.During the flight phase, the amplitude of the splitwas observed.On the basis ofthe obtainedresults, it is clear that during the run-up and take-off phases, the height of the sacrum is greater using RT, but the maximum elevation is higher using CT during the flight phase. Regarding the speed, the horizontal component is higher using RT while the vertical component is higher in CT. The angle of flexion-extension of the splits is higher in CT. From the three-dimensionality of the movement in the hip joint during the split,it is clearthat in addition to flexion-extension, abduction and external rotation also occurred. Using CT, at the time of contact and shortly after take-off,angular acceleration during the flexion of the legregistered higher values. Therefore, it is assumed that limb momentum is more important when using CT than RT.Thus, it is assumed that the technical-coordinative elementacquired through the rhythmic gymnastics workouts, which occurs in chassè, considerably affects the efficacy of execution of the split leap. Thus, the use of descriptive analysis is essential to understand the kinematics of sports movement and is fundamental to structure training.